2015
DOI: 10.1007/s11432-015-5305-y
|View full text |Cite
|
Sign up to set email alerts
|

Linear complexity problems of level sequences of Euler quotients and their related binary sequences

Abstract: The Euler quotient modulo an odd-prime power p r (r > 1) can be uniquely decomposed as a p-adic number of the formwhere 0 ≤ a j (u) < p for 0 ≤ j ≤ r − 1 and we set all a j (u) = 0 if gcd(u, p) > 1. We firstly study certain arithmetic properties of the level sequences (a j (u)) u≥0 over F p via introducing a new quotient. Then we determine the exact values of linear complexity of (a j (u)) u≥0 and values of k-error linear complexity for binary sequences defined by (a j (u)) u≥0 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Firstly, the distribution of vectors of consecutive Euler-Fermat quotients modulo a composite was described in [9]. Trace representations of sequences deduced from Euler quotients modulo a prime power were studied in [10]. Furthermore, the -error linear complexity of binary sequences deduced from Euler quotients modulo a prime power was determined [11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the distribution of vectors of consecutive Euler-Fermat quotients modulo a composite was described in [9]. Trace representations of sequences deduced from Euler quotients modulo a prime power were studied in [10]. Furthermore, the -error linear complexity of binary sequences deduced from Euler quotients modulo a prime power was determined [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Winterhof generalized the Fermat quotient to the polynomial quotient in [7]. Then the k-error linear complexity was determined for binary sequences derived from the polynomial quotient modulo a prime [5] or its power [22], respectively. In [23], a series of optimal families of perfect polyphase sequences were derived from the array structure of Fermat-quotient sequences.…”
mentioning
confidence: 99%
“…We give an example of generalized cyclotomic binary sequences (applying Theorem 3) in Appendix C.4.1 and found that such sequences are not "good" pseudorandom sequences. In recent years, the pseudorandom sequences derived from Fermat quotients have attracted extensive attention [7][8][9], these sequences are of high linear complexity, and the problem of their k-error linear complexity deserves further study. We also give another numerical example (applying Theorem 4) in Appendix C.4.2.…”
mentioning
confidence: 99%